THE EFFECT OF TEACHER REWARD AND SOCIAL SUPPORT ON THE LEARNING RESILIENCY OF CLASS XI STUDENTS AT SMA NEGERI 1, ASAHAN DISTRICT - Cynthia Fitri Kautsar; Asih Menanti; Nadra Ideyani Vita (RADJA PUBLIKA, 2023)
Learning resilience describes the efforts of students in overcoming negative experiences or challenges that suppress and hinder the learning process, so that they are able to adapt and carry out every academic demand properly. To build the success of the learning process educators must establish the learning resilience of students during the pandemic. This study aims to analyze the effect of rewards and social support on student learning resilience. The research method used is a quantitative research method with an ex post facto research design. The research was conducted at SMA Negeri 1 Kisaran, Asahan Regency. The total population of the study was 252 students and the number of samples taken from the population was 155 people. The sampling technique used is proportional random sampling technique. The results showed a positive and significant effect of rewards on the resilience of Class XI students at SMA Negeri 1 Asahan Regency by 20.9%. Then there is a significant positive effect of social support on the resilience of Class XI Students of SMA Negeri 1 Asahan Regency of 31.60%. And there is also a significant positive effect of rewards and social support together on the resilience of Class XI students at SMA Negeri 1 Asahan Regency by 44.3% while the remaining 55.7% comes from other variables outside the variables of this study.